PEMBUATAN APLIKASI DATABASE SELEKSI PENERIMAAN KARYAWAN PADA PERUM PERUMNAS DENGAN MENGGUNAKAN MICROSOFT VISUAL BASIC 6.0 - Sumbaryadi, Achmad (Universitas Dirgantara Marsekal Suryadarma, 2017)
Data is a set of raw materials that have not been processed, so do not have a meaning and can not be used by users. So to do the data processing that is required quickly and accurately called the media system. PERUMNAS program has the reception of each new employee a certain period, the number of data of the applicants and the entry requirements required a system that can store and process data and print reports if needed at any time by the head.